Connexin 43 impacts on mitochondrial potassium uptake - Boengler, Kerstin; Ungefug, Elvira; Heusch, Gerd; Leybaert, Luc; Schulz, Rainer (Frontiers in Pharmacology, 2013)
In cardiomyocytes, connexin 43 (Cx43) forms gap junctions and unopposed hemichannels at the plasma membrane, but the protein is also present at the inner membrane of subsarcolemmal mitochondria. Both inhibition and genetic ablation of Cx43 reduce ADP-stimulated complex 1 respiration. Since mitochondrial potassium influx impacts on oxygen consumption, we investigated whether or not inhibition or ablation of mitochondrial Cx43 alters mitochondrial potassium uptake. Subsarcolemmal mitochondria were isolated from rat left ventricular (LV) myocardium and loaded with the potassium-sensitive dye PBFI. Intramitochondrial potassium was replaced by TEA (tetraethylammonium). Mitochondria were incubated under control conditions or treated with 250 µM Gap19, a peptide that specifically inhibits Cx43-dependent hemichannels at plasma membranes. Subsequently, 140 mM KCl was added and the slope of the increase in PBFI fluorescence over time was calculated. The slope of the PBFI fluorescence of the control mitochondria was set to 100%. In the presence of Gap19, the mitochondrial potassium influx was reduced from 100±11.6 % in control mitochondria to 65.5±10.7 % (n=6, p<0.05). In addition to the pharmacological inhibition of Cx43, potassium influx was studied in mitochondria isolated from conditional Cx43 knockout mice. Here, the ablation of Cx43 was achieved by the injection of 4-hydroxytamoxifen (Cx43Cre-ER(T)/fl + 4-OHT). The mitochondria of the Cx43Cre-ER(T)/fl + 4-OHT mice contained 3±1% Cx43 (n=6) of that in control mitochondria (100±11%, n=8, p<0.05). The ablation of Cx43 (n=5) reduced the velocity of the potassium influx from 100±11.2 % in control mitochondria (n=9) to 66.6±5.5 % (p<0.05). Taken together, our data indicate that both pharmacological inhibition and genetic ablation of Cx43 reduce mitochondrial potassium influx.